Cardanol benzoxazine‐Sulfur Copolymers for Li‐S batteries: Symbiosis of Sustainability and Performance. Issue 3 (22nd March 2016) - Shukla, Swapnil; Ghosh, Arnab; Sen, Uttam Kumar; Roy, Prasun Kumar; Mitra, Sagar; Lochab, Bimlesh
Abstract: A sulfur‐rich copolymer is synthesized via a sustainable, eco‐friendly approach using two major wastes namely, elemental sulfur (industrial waste) and cardanol (agro waste) and its application as cathode active material in Li−S battery. The presence of chemically bound sulfur (90 wt%) utilising cardanol (10 wt%) derivative in the copolymer (S90) showed a reduction in the active material dissolution into the electrolyte. In addition, the organic sulfur units get dispersed into the insoluble/insulating Li2 S2 /Li2 S phase and thus found to suppress their irreversible deposition. Li−S battery based on S90/multi‐walled carbon nanotubes (MWCNT) (10 wt%) exhibited a reversible capacity of 1302 mAh g −1 at 2 nd cycle, maintaining a high reversible capacity of 928 mAh g −1 after 70 cycles at a relatively constant coulombic efficiency over 99 % at current rate of 200 mA g −1 . At 1000 mA g −1 current rate, the composite cathode delivered a reversible capacity of 697 mAh g −1 at 2 nd cycle and retained 75 % of its initial capacity even after 180 cycles. Abstract : Cardanol benzoxazine was utilized to synthesize sulfur based copolymer (S90) with high sulfur content (90 wt%). Synthetic methodology is based on utilization of agro and industrial wastes via inverse vulcanization route. The S90/Multi‐walled carbon nanotubes (MWCNT, 10 wt%) derived Lithium‐Sulfur (Li−S) battery exhibited a reversible capacity of 1302 mAh g −1 at 2 nd cycle, maintaining a high reversible capacity of 928 mAh g −1 after 70 cycles at a relatively constant coulombic efficiency over 99 % at current rate of 200 mA g −1 .